Origin stories in CSR: genesis of CSR at British American Tobacco - Coombs, Timothy (Corporate Communications: An International Journal, 2017)
Purpose Graphic novels have a concept known as the origin story. The origin story is background information on how a hero or villain came into being. The purpose of this paper is to explore the origin story of corporate social responsibility at British American Tobacco (BAT). The CSR origin story is unpacked by examining corporate documents from BAT that discuss the initial development of the company’s CSR program. The BAT documents are part of the Legacy Tobacco Documents Library (LTDL), a searchable, digital archive developed and managed by the University of California, San Francisco. It contains 85,569,326 pages in 14,360,422 documents. The library was created as part of the tobacco company settlement of a major law suit in the USA. Design/methodology/approach For this case study, the authors searched the archive for documents from BAT that had the key words “corporate social responsibility.” The documents were then analyzed using qualitative content analysis to identify key themes related to BAT’s created of its CSR programs. Findings The two dominant themes were business case BAT made for CSR and the environmental factors that shaped CSR. The business case had sub-themes of the new operating environment and reinforcing employees. The environmental sub-themes were the importance of NGOS and the top issues to be addressed in CSR efforts. The themes helped to explain why BAT was engaging in CSR, the factors shaping the start of its CSR programs, and the issues it intended to address through CSR. Research limitations/implications The analysis is limited to one organization and does not include interviews to go with the archived documents. Practical implications The paper considers the implications of the analysis for theory and practice for internal CSR communication. Originality/value The documents provide a rare glimpse inside a corporate decision to begin a CSR program and how the managers “talked” about CSR. Instead of examining external CSR communication, it examines the early days of internal CSR communication at a specific firm. The yields of the document analysis provide insights into how BAT conceptualized CSR and communicated the rationale for creating a CSR program internally. Research has relied primarily upon speculation of corporate motives or corporate public discourse designed to frame their CSR efforts. The internal documents provide an unfiltered examination of the motives for a CSR program. This allows us to better understand why a CSR program was created including the motives, targets, and desired outcomes.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTEwOC9jY2lqLTAxLTIwMTYtMDAwNw